Pengaruh Pendidikan, Pelatihan Kerja, Pengalaman Kerja terhadap Produktivitas Kerja Karyawan pada PT. Pacific Angkasa Abadi - Tiara Ulla Ananda Putri; Maulidyah Amalina Rizqi (MAMEN: Jurnal Manajemen, 2024)
The Background to this research is that in the last five years employee work productivity has decreased from 2018 – 2022. This research aims to test the influence of education, job training, and work experience of employees work productivity at PT PACIFIC ANGKASA ABADI. This research uses a quantitative methods. The population in this research was 45 employees, while the sampling used was using non-probability sampling techniques, namely using saturated sampling, the reason is because the sample in the research is relatively small, which is less than 100 people, it is mandatory to take all of the population, the sample in this study is 45 employees. The analysis technique uses instrument testing, classical assumption testing, and hypothesis testing. For testing tool, use the Statistical Package for the Social Sciences (SPSS). The results of this research show that education has a positive and significant effect on productivity, job training has a positive and significant effect on productivity, and work experience has a positive and significant effect on productivity.